ANALISIS STRATEGI DINAS TENAGA KERJA DAN TRANSMIGRASI MEWUJUDKAN PEMUDA SIAP KERJA DALAM MENGATASI PENGANGGURAN DI KABUPATEN SAMBAS - Al Azhari; Annisa Rahmadanita (Jurnal Konstituen, 2025)
Indonesia is ranked second in terms of the highest youth unemployment rate in Southeast Asia. The Open Unemployment Rate of Sambas Regency in 2023 is 5.04%.. The Sambas Regency Manpower and Transmigration Office held a flagship program in the form of a work-ready youth program, which is a program to encourage increased community income. However, the implementation of the program has not yet reached the target, namely based on BPS data, the Open Unemployment Rate (TPT) of Sambas Regency 2020-2023 is still high. This research aims to analyze the right strategy for the Manpower and Transmigration Office in overcoming unemployment problems in the youth ready-to-work program. This research is qualitative in nature. This research was analyzed using a SWOT matrix. From the SWOT matrix above, there are four strategies that can be used by the Sambas Regency Manpower and Transmigration Office in the work-ready youth program, namely: SO Strategy, WO Strategy, ST Strategy and WT Strategy which amounts to 13 new strategies that can be used in the work-ready youth program by the Sambas Regency Manpower and Transmigration Office. In conclusion, referring to the 13 strategies, there are three classifications of strategies, namely the first strategy classification is strengthening the human resource capacity of prospective workers; the second strategy classification is strengthening collaboration with various elements related to programs and activities that have the potential to reduce unemployment; the third strategy classification is improving infrastructure and adequate budget priorities.